Bod khul gyi chos sde grags can khag gi dpe rñiṅ dkar chag - Shes-rab-dpal-ldan (Mi rigs dpe skrun khaṅ, 2011)
Catalog of rare texts held by several of the largest monasteries across the Tibetan Plateau
Text tibet. - Katalog seltener Werke aus tibetischen Klosterbibliotheken
Keywords: Bibliografie; Katalog; Rare books / Tibet Region / Catalogs; Tibetan literature / Bibliography / Catalogs; Buddhist literature; Tibetan / Bibliography / Catalogs; Literatur; Klosterbibliothek; Handschrift